Sabin alun: And other popular legends of the Karbis - Phukan Ch Phangcho; PHANGCHO (Phukan Ch) (Assam Dubori Niyor Creations, 2002)
Karbii Ramayan
Keywords: Karbi Ramayana; Assamese Tr in English; Legends of Karbis